2003
DOI: 10.1016/s1468-6996(03)00027-5
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and luminescent properties of Eu-doped BaTiO3 thin films by sol–gel process

Abstract: Eu-doped BaTiO 3 thin films with a pseudo-cubic perovskite structure were successfully fabricated on magnesia substrates at low temperature by using a high-concentration sol-gel process, in which the newly developed gel-aging process on substrate was employed. Film microstructure, crystallinity, sintering properties and photoluminescence (PL) were investigated. The xerogel thin films exhibited strong PL associated with Eu 3þ ions under ultraviolet excitation at room temperature; the PL was visible to naked eye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Other than that, from Figure 5, it was also observed that the emission peak intensity increased as the sintering temperature increased. This increment occurred as a result from the improvement of the crystallinity inside the zinc silicate glass and glass-ceramics sample [30]. When heat is applied to the zinc silicate sample, this will cause changes in the donor and the acceptor levels of the electron, in which it is interrelated with the number of electronic defects.…”
Section: Discussionmentioning
confidence: 99%
“…Other than that, from Figure 5, it was also observed that the emission peak intensity increased as the sintering temperature increased. This increment occurred as a result from the improvement of the crystallinity inside the zinc silicate glass and glass-ceramics sample [30]. When heat is applied to the zinc silicate sample, this will cause changes in the donor and the acceptor levels of the electron, in which it is interrelated with the number of electronic defects.…”
Section: Discussionmentioning
confidence: 99%
“…The emission spectra emitted at heat treatments of 700, 800 and 900 • C show that the intensity of the emission is increased with the increase of heat-treatment temperatures. This is because of the improvement in crystallinity inside the sample as the heat-treatment temperature progresses [41]. Moreover, the intensity variation depends on some aspects, which include the structural modification of glass matrix, the amount of the luminescent ions and the wavelength of the excitation source used [42].…”
Section: Photoluminescence Analysismentioning
confidence: 99%
“…1,2 Unlike the traditional Pb(Zr,Ti)O 3 (PZT), 3,4 which is toxic to the environment due to the presence of Pb, tetragonal Barium Titanate (BaTiO 3 or BT) is one of the most important green ferroelectric materials and has been extensively used in many areas such as biosensors, 5 bioimaging, 6,7 and thermistors 8 due to its unique ferroelectric, optical, piezoelectric, dielectric, and electrochemical properties. 914 BT crystals have five crystalline phases including rhombohedral, orthorhombic, tetragonal, cubic and hexagonal phases. Different phases of BT crystals have different applications based on their unique photo-refractive and electro-optical properties.…”
Section: Introductionmentioning
confidence: 99%